ANALISIS PEMANFAATAN AI (ARTIFICIAL INTELLIGENCE) DALAM MENINGKATKAN KREATIVITAS GURU KELAS VI DI SD NEGERI 05 PALEMBANG - Karinta Putri, Azra; Farizal Imansyah; Nofroza Yelli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted to analyze the use of Artificial Intelligence (AI) in enhancing the creativity of sixth-grade teachers at SD Negeri 05 Palembang. The primary focus of this study is to examine the extent to which this technology can serve as a catalyst for teachers to develop more flexible and engaging learning innovations for elementary school students. This study employed a descriptive qualitative method using a case study approach. Data were collected through direct observation, in-depth interviews with sixth-grade teachers, and documentation of learning products that utilized AI tools. Subsequently, the collected data were analyzed using the Miles and Huberman analytical model. The findings indicate that the implementation of AI-based tools, such as Canva Magic Design and other automated content-creation platforms, has proven to help teachers work more efficiently in developing creative teaching materials. In addition, this technology also enables more diverse visual exploration tailored to students’ characteristics. Nonetheless, this study also identified barriers in the form of uneven levels of teachers’ digital literacy and limited supporting facilities at the school. Overall, AI has proven effective in supporting teachers’ pedagogical creativity; however, ongoing technical support is needed to ensure its optimal and equitable use